2007
DOI: 10.5194/hess-11-1897-2007
|View full text |Cite
|
Sign up to set email alerts
|

Rapid channel incision of the lower Pearl River (China) since the 1990s as a consequence of sediment depletion

Abstract: Abstract. This paper reported a dramatic channel incision (>10 m in the deepest cut) during the past 10 y or so in the lower Pearl River, the second largest river in terms of water discharge in China. The channel incision had caused changes both in the channel geometry as well as in the river hydraulics. Also, the water exchange between the two major tributaries of the Pearl River, the Xijiang and Beijiang, had been significantly changed due to the channel incision. The rapid channel incision was principally t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 32 publications
(32 reference statements)
0
39
0
Order By: Relevance
“…Before mid-1980s, however, the scouring and filling processes of the river channels are in dynamic balances or in slight deposition processes. The river channels in the lower Pearl River basin were greatly altered due to in-channel dredging and levee construction after about mid-1980s, resulting in decreasing water level (Lu et al, 2007). Lu et al (2007) also indicated that slight increase in water discharge and significant decrease in sediment load since the early 1990s in both the West River and North River also likely contributed to the observed dramatic river bed downcutting to some extent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Before mid-1980s, however, the scouring and filling processes of the river channels are in dynamic balances or in slight deposition processes. The river channels in the lower Pearl River basin were greatly altered due to in-channel dredging and levee construction after about mid-1980s, resulting in decreasing water level (Lu et al, 2007). Lu et al (2007) also indicated that slight increase in water discharge and significant decrease in sediment load since the early 1990s in both the West River and North River also likely contributed to the observed dramatic river bed downcutting to some extent.…”
Section: Discussionmentioning
confidence: 96%
“…Massive incision of river channel has caused a significant change in channel geometry. Lu et al (2007) showed notable increases in the cross-section area accompanying the downcuts of river channels at all the Gaoyao station, Makou station and the Sanshui station. Based on the time when the shifts of the double mass curves start at the stations in the West River and North River, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the estimated 870 million cubic metres of sand excavated between 1986 and 2003 in the rivers of the Pearl basin resulted in severe lowering of river channels, bank instability and threats to infrastructure, changes in the divided flow ratio between various water courses, modification of saltwater intrusion levels and a limitation of the freshwater supply. The extraction rate was much greater than the replenishment rate, a situation aggravated because sediment fluxes depleted dramatically due to the combined effects of declining rainfall, dam construction, water diversion, reforestation and afforestation (Lu et al, 2007, Luo et al, 2007.…”
mentioning
confidence: 99%
“…Therefore, the currently agreed minimum flow requirements at Wuzhou and Sixianjiao may not be sufficient to combat salt intrusion in the future. Moreover, channel incision can contribute to saltwater intrusion and subsequent water shortage in the delta due to increasing channel depth and sea level (Lu et al, 2007). The rapid channel incision was mainly the result of extensive sand mining in the lower reaches of the Pearl River.…”
Section: Q2: Can Water Allocation Reduce Saltwater Intrusion In the Pmentioning
confidence: 99%